PROTOTYPE SISTEM CO DETECTOR PADA CABIN MOBIL - Alfian Nurfauzi (Jurnal Pendidikan Vokasi Otomotif, 2020)
Carbon monoxide gas is a gas from combustion and this gas can enter vehicles, especially cars, so that it can endanger the safety of passengers. Carbon monoxide is a gas that is odorless, colorless and tasteless so that it cannot be felt by the human senses but is dangerous because it can inhibit the distribution of oxygen in the body. Based on this, this research was conducted to develop a carbon monoxide detector prototype in the vehicle cabin to detect carbon monoxide. The development process consists of needs analysis, making tool designs, simulating tool performance using software and making prototypes. The prototype not only detects carbon monoxide in the car but also circulates the air inside the car so that toxic gases can come out when the detected carbon monoxide exceeds the threshold.